Impacts of Navy Sonar on Whales and Dolphins: Now beyond a Smoking Gun? - Parsons, E. C. M. (Frontiers in Marine Science, 2017)
The risks military sonar poses to cetaceans received international attention with a highly-publicized mass stranding of Cuvier’s beaked whales (Ziphius cavirostris), Blainville’s beaked whales (Mesoplodon densirostris) and northern minke whales (Balaenoptera acutorostrata) in the Bahamas in 2000. This was the first time that the US Government determined a stranding to be the result of mid-frequency active sonar use. Subsequently attention has been drawn to other mass strandings coincident with naval exercises, including events preceding the 2000 mass stranding. The list of species for which mass strandings have been linked to naval exercises has also increased to include other beaked whales, dwarf and pygmy sperm whales (Kogia spp.), pilot whales (Globicephala spp.), several dolphin species (Stenella sp. and Delphinus delphis) and harbor porpoises (Phocoena phocoena). In particular, there have been several mass strandings in the northern Indian Ocean coincident with naval exercises - including one of the largest (200-250 dolphins) - which have received little attention. Changes in beaked whale behaviour, including evasive manoeuvring, have been recorded at received levels below <100 dB re 1µPa (rms) and mass stranding may occur at received levels potentially as low as 150–170 dB re 1 µPa. There is strong scientific evidence to suggest that a wide range of whale, dolphin and porpoise species can also be impacted by sound produced during military activities, with significant effects occurring at received levels lower than previously predicted. Although there are many stranding events that have occurred coincident with the presence of naval vessels or exercises, it is important to emphasize that even the absence of strandings in a region does not equate to an absence of deaths, i.e., absence of evidence does not mean evidence of absence. Strandings may be undetected, or be unlikely to be observed because of a lack of search effort or due to coastal topography or characteristics. There may also be “hidden” impacts of sonar and exercises not readily observable (e.g., stress responses). Due to the level of uncertainty related to this issue, ongoing baseline monitoring for cetaceans in exercise areas is important and managers should take a precautionary approach to mitigating impacts.